2007
DOI: 10.1111/j.1365-2648.2007.04310.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of school nursing provision in the UK

Abstract: Investment in recruitment and education is required if school nurses are to meet increasing demands and fulfil their public health role. The low percentage of school nurses aged under 30 years may reflect lack of a career pathway and understanding of school nursing. The findings enable national and international comparisons in terms of numbers, size of caseload, age, qualifications, terms of employment and activities and functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…The number of schools under an elementary school nurse's responsibility ranged from 1 to 12, and the number of students per ESN was twice the recommended ratio in the United States [46]. Some researchers have suggested that a low percentage of school nurses under 30 years of age may reflect lack of a career pathway and understanding of school nursing [47]. …”
Section: Resultsmentioning
confidence: 99%
“…The number of schools under an elementary school nurse's responsibility ranged from 1 to 12, and the number of students per ESN was twice the recommended ratio in the United States [46]. Some researchers have suggested that a low percentage of school nurses under 30 years of age may reflect lack of a career pathway and understanding of school nursing [47]. …”
Section: Resultsmentioning
confidence: 99%
“…At present, most of the primary schools in Hong Kong do not have the resources to employ a school nurse, and not many nurses in Hong Kong are prepared to work in school health. If school nurses are to meet the increasing demands to fulfil their public health role for primary school students, investment in recruiting and education is required to increase the number of qualified school nurses (Merrell et al. 2007).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…National surveys of school nurses’ work have been undertaken in Sweden, Scotland, and Wales, with staff responses emphasizing that involvement in mental health work forms a key part of their role (Merrell et al. 2007, Clausson et al.…”
Section: Introductionmentioning
confidence: 99%